ROLE OF PERCEIVED CONSUMER EFFECTIVENESS (PCE) ON GREEN PURCHASE BEHAVIOUR WITH REFERENCE TO KANNUR DISTRICT - P. C, Sumesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Perceived Consumer Effectiveness (PCE) plays a pivotal role in influencing green purchase behavior, particularly in regions where environmental awareness is gradually increasing. This study investigates the relationship between PCE and green purchase behavior in the context of consumers from Kannur District. The research explores how individuals’ belief in their ability to positively impact the environment through eco-friendly purchasing decisions shapes their buying patterns. Using quantitative methods, the study highlights the significant contribution of PCE in motivating sustainable consumption. Key findings indicate that consumers with higher levels of PCE are more likely to purchase green products, driven by environmental concerns, social influence, and perceived product value. The results underscore the importance of enhancing PCE through targeted awareness campaigns and policies to foster environmentally responsible consumer behavior. This research provides valuable insights for marketers, policymakers, and environmental organizations aiming to promote green consumption in the region